Fetal, infant and ophthalmic medical image analysis : International Workshop, FIFI 2017, and 4th International Workshop, OMIA 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, Proceedings /: International Workshop, FIFI 2017, and 4th International Workshop, OMIA 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, Proceedings. (2017) - Unknown
No abstract available